Experimental study of tribological characteristics of promising self-lubricating materials for high-speed friction units - N. A. Raikovskiy; A. M. Kalashnikov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The paper considers a technique and a stand for experimental study of the tribological characteristics of materials for high-speed «dry» friction units that implement the «finger-disk» friction scheme. As a result of experimental studies, the tribological characteristics of traditional and promising domestic and foreign self-lubricating materials were determined. A significant dependence of the friction-wear characteristics of self-lubricating materials of high-speed «dry» friction units on the sliding speed has been established. At the same time, the best tribological characteristics in the entire range of sliding speeds from 10 m/s to 40 m/s correspond to the Kryolon-3 material.